Analisis Penggunaan Bahasa Indonesia pada Konten Reels Edukatif di Instagram Bagi Remaja - Siahaan, Meylan; Ginting, Piladelpia Trifosa Br; Rahmadani, Sari; Lubis, Ruth Nila Sari; Sianipar, Sinta; Siallagan, Lasenna (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The use of Instagram Reels as a medium for disseminating educational information is increasing among teenagers. This situation makes the quality of Indonesian language use in educational content important to study because the language used not only influences the effectiveness of information delivery but also plays a role in shaping the language habits of the younger generation in digital media. This study aims to analyze the effective use of Indonesian in educational Instagram Reels content for teenagers. The study used a qualitative descriptive approach with documentation techniques on 15 Instagram Reels content containing educational material from various fields. Data were analyzed based on four aspects: language standardization, sentence effectiveness, the use of foreign language mixtures, and clarity of meaning. The results showed that most of the content met the aspects of sentence effectiveness and clarity of meaning through the use of short, clear, and easy-to-understand sentences. However, the use of non-standard language, such as gak (no), udah (already), aja (aja), and kaya (kayak), as well as several English terms, such as working memory (mood), like (like), and follow (follow), were still found. These findings indicate that the language used in Instagram Reels content tends to adapt to the characteristics of social media and the teenage audience. Therefore, educational content creators need to maintain a balance between communicative language and adherence to Indonesian language rules so that social media can function as a means of education as well as fostering good and correct language use.